2015
DOI: 10.4187/respcare.03709
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function Testing and Outcomes in Subjects With Heart Failure Listed for Heart Transplantation

Abstract: BACKGROUND: Impaired spirometric parameters have been reported in patients with stage C heart failure and portend worse outcomes in these patients. The impact of spirometric parameters on outcomes in patients with stage D heart failure listed for heart transplantation is unknown. METHODS: We collected data on consecutive subjects listed for heart transplantation and examined the association of FEV 1 , FVC, and FEV 1 /FVC with (1) death or left ventricular assist device implantation (primary end point) and (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…However, a smaller study found no association between preoperative lung function and posttransplant survival. 14 It is important to consider that the reduction in 30-day survival observed in this study was modest compared with other risk factors, and may not be prohibitive to proceeding with transplantation. For example, the absolute difference in early mortality is much less than the risk of retransplantation or transplantation for congenital heart disease, 15 but shares similar short-term risk magnitude with other traditional risk factors such as increasing recipient age, peripheral vascular disease, and diabetes.…”
Section: -Yearmentioning
confidence: 80%
“…However, a smaller study found no association between preoperative lung function and posttransplant survival. 14 It is important to consider that the reduction in 30-day survival observed in this study was modest compared with other risk factors, and may not be prohibitive to proceeding with transplantation. For example, the absolute difference in early mortality is much less than the risk of retransplantation or transplantation for congenital heart disease, 15 but shares similar short-term risk magnitude with other traditional risk factors such as increasing recipient age, peripheral vascular disease, and diabetes.…”
Section: -Yearmentioning
confidence: 80%
“…ILD often results in characteristics changes on PFT, including reductions in TLC, FVC and/or DLCO [11]. However, isolated or composite reductions in these metrics can be observed in numerous unrelated disease states [15][16][17][18][19], which may explain why mention of ILD was less strongly associated with pulmonology referral in these patients. Systematic screening of PFTs followed by a recommendation for chest CT or pulmonology referral when ILD features are present may facilitate a reduction in diagnostic delays observed in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has shown that ventilatory indexes were associated with mortality in early but not in late stage of HFrEF. 35 PH was found to interact with the prognostic role of pulmonary function in long‐term outcomes in patients with HFrEF, regardless of the functional status. For patients with severe HF and concomitant PH, Ingle et al have reported the lower contribution of spirometric variables to the exercise capacity, 36 as well as insufficient power to predict long‐term outcomes.…”
Section: Discussionmentioning
confidence: 93%